To solve the equation \(-x + \frac{1}{4}y + \frac{5}{4} = 0\) for \(y\) and express it in the desired format, let’s follow these steps:
-
First, isolate \(y\): \[ \frac{1}{4}y = x - \frac{5}{4} \]
-
Multiply both sides by 4 to eliminate the fraction: \[ y = 4x - 5 \]
Now, you mentioned setting \(x = 5\) to find the corresponding value of \(y\):
- Substitute \(x = 5\) into \(y = 4x - 5\): \[ y = 4(5) - 5 = 20 - 5 = 15 \]
So, the equations obtained are: \[ y = 4x - 5, \quad y = 15 \]
These satisfy your requirements:
- The variable \(y\) is on the left, before the constant.
- There are no mixed fractions or decimals.
- Each equation is expressed in proper descending order.